Environmental accounting in medical waste management from a Pangkalbalam Community Health Center - Fersari, Tika Pustika; Vipul Kumar Gautam; Jaya Gautam (Universitas Pendidikan Nasional, 2026)
This research examines the implementation of environmental accounting in medical waste management at a non-inpatient primary healthcare facility, namely the Pangkalbalam Community Health Center in Pangkalpinang City, Indonesia. Despite increasing regulatory pressure on healthcare institutions to manage environmental impacts, the integration between waste management practices and accounting systems remains underexplored, particularly at the primary care level. This research aims to analyze how environmental costs are identified, recognized, measured, presented, and disclosed within the context of medical waste management. A qualitative approach was employed, combining direct observation, document analysis, and in-depth interviews with key informants, including sanitation staff and financial officers. The findings reveal that while operational waste management practices are generally implemented in compliance with regulatory requirements, environmental accounting remains partial, fragmented, and predominantly administrative. Environmental costs are recognized and measured but not systematically classified or disclosed as distinct accounts, resulting in limited cost visibility and weak support for decision-making. Furthermore, the cost structure is predominantly reactive, characterized by internal failure costs, with minimal integration of prevention and detection mechanisms. This research demonstrates that environmental accounting practices in non-inpatient primary healthcare facilities are not merely underdeveloped but structurally distinct, shaped by limited institutional capacity and relatively low external pressures. Consequently, accounting practices remain cash-based, administrative, and weakly integrated into strategic management. These findings highlight the need for more integrated, transparent, and proactive environmental accounting frameworks to support sustainability in primary healthcare settings.